2002
DOI: 10.1179/acb.2002.076
|View full text |Cite
|
Sign up to set email alerts
|

Nouvelles Drogues De « Rave-Parties » : Ketamine Et Prolintane

Abstract: "Rave parties", all-night dance parties based on "techno" music, represent an increasing phenomenon in France. "Rave drugs" refers to a wide variety of drugs used by the young participants owing to their hallucinogenic or stimulant effects. Uncertainties about the sources of these substances, the possible contaminants and the multiplicity of the associations make it difficult to evaluate the toxic consequences that might be expected in this particular context. This report presents toxicological cases documente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
2
0
3
Order By: Relevance
“…Several studies have demonstrated the AMPH-like central stimulant character of prolintane (Hollister & Gillespie, 1970; Kuitunen, Kärkkäinen & Ylitalo, 1984; Nicholson, Stone & Jones, 1980). Now, there are recent reports of prolintane abuse (Gaulier, Canal, Pradeille, Marquet & Lachâtre, 2002; Kyle & Daley, 2007; Payá, Guisado, Vaz & Crespo-Facorro, 2002). …”
Section: Amphetamine (Ie Phenylisopropylamine; Pia) Analogsmentioning
confidence: 99%
“…Several studies have demonstrated the AMPH-like central stimulant character of prolintane (Hollister & Gillespie, 1970; Kuitunen, Kärkkäinen & Ylitalo, 1984; Nicholson, Stone & Jones, 1980). Now, there are recent reports of prolintane abuse (Gaulier, Canal, Pradeille, Marquet & Lachâtre, 2002; Kyle & Daley, 2007; Payá, Guisado, Vaz & Crespo-Facorro, 2002). …”
Section: Amphetamine (Ie Phenylisopropylamine; Pia) Analogsmentioning
confidence: 99%
“…Aangezien er een sterke amnesie optreedt bij de mens, herinnert het dier zich achteraf hoogstwaarschijnlijk ook niet wat er gebeurd is. Omwille van het hallucinogeen effect worden deze producten trouwens ook misbruikt als 'party-drug' (Gaulier et al, 2002).…”
Section: Inleidingunclassified
“…Wanneer met detomidine of romifidine wordt gewerkt, is dit niet noodzakelijk. Gezien het hallucinogeen effect van ketamine (Gaulier et al, 2002) is het niet aan te raden de anesthesie langer dan 30 minuten op deze manier te onderhouden of een totale extra dosis ketamine van meer dan 1 à 1,5 mg/kg te geven. Indien dit om een of andere reden niet vermeden kan worden, wordt het paard het beste bijkomend gesedeerd om de kans op een slechte recovery te verkleinen; dit bijvoorbeeld met een kwart van de originele sedatiedosis van de α2-agonist.…”
Section: Korte Algemene Anesthesie (Maximaal 30 Minuten)unclassified
“…Los consumidores de ketamina refieren un estado disociativo, como si estuviesen fuera del cuerpo, con sensación de flotación. Dicho estado puede acompañarse de experiencias que están separadas de la realidad (alucinaciones) y dificultad para moverse, que pueden prolongarse durante 24 horas 65 . Las experiencias percibidas pueden revivirse semanas o meses después del consumo (flash back) en forma análoga a lo que también produce el LSD.…”
Section: Efectosunclassified